Comparative Analysis of Gracilaria chouae Polysaccharides Derived from Different Geographical Regions: Focusing on Their Chemical Composition, Rheological Properties, and Gel Characteristics - Xiong Li; Wanzi Yao; Cebin Hu; Congyu Lin; Lijun You; Jian Mao (Gels, 2024)
Polysaccharides derived from diverse sources exhibit distinct rheological and gel properties, exerting a profound impact on their applicability in the food industry. In this study, we collected five Gracilaria chouae samples from distinct geographical regions, namely Rizhao (RZ), Lianyungang (LYG), Ningde (ND), Beihai (BH), and a wild source from Beihai (BHW). We conducted analyses on the chemical composition, viscosity, and rheological properties, as well as gel properties, to investigate the influence of chemical composition on variations in gel properties. The results revealed that the total sugar, sulfate content, and monosaccharide composition of G. chouae polysaccharides exhibit similarity; however, their anhydrogalactose content varies within a range of 15.31% to 18.98%. The molecular weight distribution of G. chouae polysaccharides ranged from 1.85 to 2.09 × 103 kDa. The apparent viscosity of the LYG and BHW polysaccharides was relatively high, whereas that of RZ and ND was comparatively low. The gel strength displayed a similar trend. BHW and LYG exhibited solid-like behavior, while ND, RZ, and BH demonstrated liquid-like characteristics at low frequencies. The redundancy analysis (RDA) analysis revealed a positive correlation between the texture profile analysis (TPA) characteristics and anhydrogalactose. The study could provide recommendations for the diverse applications of G. chouae polysaccharides derived from different geographical regions.